(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the period of what Selden, Widdowson, and Brooker call post-theory, giving us theory that is depleted due to a regularly expanding trouble in concocting any obvious arrangements, Salman Rushdie’s productive, diverse oeuvre typifies contemporary literature’s relentless propensity to avoid orders. Being in the middle of societies, customs, types, traditions and impacts, Rushdie’s work, frequently depicted as half and half and cosmopolitan, can and ought to be perused from an assortment of points of view. In a period when we are questioning the propriety of terms, for example, postcolonial and thinking about whether more broad ones, for example, transnational, transcultural, or international, would be more qualified for the present literature, this article breaks down Rushdie’s fiction between classifications as bit by bit swerving away from postcolonial postmodernism toward cosmopolitanism, with unique spotlight on The Ground beneath Her Feet, trying to address and answer the disputable question of whether we are in reality advancing toward a global(ized) literature.